Profile Of The Family Of Jamblang Rice Traders: Life Patterns, The Role Of Caring And Skills For Children In Danawinangun Village, Klangenan Cirebon - Diana, Putri; Karwati, Lilis; Hamdan, Ahmad (Learning Community : Jurnal Pendidikan Luar Sekolah, 2024)
Culinary is a field that attracts many parties, such as entrepreneurs, the consumer community, and the general public so that it becomes a business opportunity for women who sell jamblang rice in particular. The purpose of this study was to find out how the profile of the family of Jamblang rice traders is related to lifestyle, the role of parenting between mothers and fathers, and also regarding the formation of children's skills. This study uses qualitative research methods by collecting data by using interview, observation and documentation techniques. The results showed that the lifestyle of Jamblang rice traders consisted of time, interests and how to allocate money. The parenting pattern applied is permissive parenting which is defined as an enabling parenting style, and democratic, which means a parenting pattern that prioritizes discussion in making decisions for their children. The formation of children's skills is done by doing habituation and giving good examples. The conclusion of this study is that jamblang rice traders can apply parenting according to the needs of children, and can cultivate skills that are in accordance with child development